Global biogeography and diversification of a group of brown seaweeds (Phaeophyceae) driven by clade‐specific evolutionary processes. (7th January 2021) - Vieira, Christophe; Steen, Frédérique; D'hondt, Sofie; Bafort, Quinten; Tyberghein, Lennert; Fernandez‐García, Cindy; Wysor, Brian; Tronholm, Ana; Mattio, Lydiane; Payri, Claude; Kawai, Hiroshi; Saunders, Gary; et al.
Abstract: Aim: Historical processes that shaped current diversity patterns of seaweeds remain poorly understood. Using Dictyotales, a globally distributed order of brown seaweeds as a model, we test if historical biogeographical and diversification patterns are comparable across clades. Dictyotales contain some 22 genera, three of which, Dictyota, Lobophora and Padina, are exceptionally diverse. Specifically, we test whether the evolutionary processes that shaped the latitudinal diversity patterns in these clades are in line with the tropical conservatism, out‐of‐the‐tropics or diversification rate hypotheses. Location: Global coastal benthic marine environments. Taxon: Dictyotales (Phaeophyceae). Methods: Species diversity was inferred using DNA‐based species delineation, addressing cryptic diversity and circumventing taxonomic problems. A six‐gene time‐calibrated phylogeny, distribution data of 3, 755 specimens and probabilistic modelling of geographical range evolution were used to infer historical biogeographical patterns. The phylogeny was tested against different trait‐dependent models to compare diversification rates for different geographical units as well as different thermal affinities. Results: Our results indicate that Dictyotales originated in the Middle Jurassic and reach a current peak of species diversity in the Central Indo‐Pacific. Ancestral range estimation points to a southern hemisphere origin of Dictyotales corresponding to the tropical southern Tethys Sea. Our results demonstrate that diversification rates were generally higher in tropical regions, but increased diversification rates in different clades are driven by different processes. Our results suggest that three major clades underwent a major diversification burst in the early Cenozoic, with Dictyota and Padina expanding their distribution into temperate regions while Lobophora retained a predominantly tropical niche. Main conclusions: Our results are consistent with both the tropical conservatism hypothesis, in which clades originate and remain in the tropics ( Lobophora ), and the out‐of‐the‐tropics scenario, where taxa originate and expand towards the temperate regions while preserving their presence in the tropics ( Dictyota, Padina ).